Antidiabetic Property of Symplocos cochinchinensis Is Mediated by Inhibition of Alpha Glucosidase and Enhanced Insulin Sensitivity - Antu, Kalathookunnel Antony; Riya, Mariam Philip; Mishra, Arvind; Anilkumar, Karunakaran S.; Chandrakanth, Chandrasekharan K.; Tamrakar, Akhilesh K.; Srivastava, Arvind K.; Raghu, K. Gopalan (PLOS ONE, 2014)
The study is designed to find out the biochemical basis of antidiabetic property of Symplocos cochinchinensis (SC), the main ingredient of ‘Nisakathakadi’ an Ayurvedic decoction for diabetes. Since diabetes is a multifactorial disease, ethanolic extract of the bark (SCE) and its fractions (hexane, dichloromethane, ethyl acetate and 90% ethanol) were evaluated by in vitro methods against multiple targets relevant to diabetes such as the alpha glucosidase inhibition, glucose uptake, adipogenic potential, oxidative stress, pancreatic beta cell proliferation, inhibition of protein glycation, protein tyrosine phosphatase-1B (PTP-1B) and dipeptidyl peptidase-IV (DPP-IV). Among the extracts, SCE exhibited comparatively better activity like alpha glucosidase inhibition (IC50 value-82.07±2.10 µg/mL), insulin dependent glucose uptake (3 fold increase) in L6 myotubes, pancreatic beta cell regeneration in RIN-m5F (3.5 fold increase) and reduced triglyceride accumulation (22% decrease) in 3T3L1 cells, protection from hyperglycemia induced generation of reactive oxygen species in HepG2 cells (59.57% decrease) with moderate antiglycation and PTP-1B inhibition. Chemical characterization by HPLC revealed the superiority of SCE over other extracts due to presence and quantity of bioactives (beta-sitosterol, phloretin 2′glucoside, oleanolic acid) in addition to minerals like magnesium, calcium, potassium, sodium, zinc and manganese. So SCE has been subjected to oral sucrose tolerance test to evaluate its antihyperglycemic property in mild diabetic and diabetic animal models. SCE showed significant antihyperglycemic activity in in vivo diabetic models. We conclude that SC mediates the antidiabetic activity mainly via alpha glucosidase inhibition, improved insulin sensitivity, with moderate antiglycation and antioxidant activity.